Tolvaptan use in cancer patients with hyponatremia due to the syndrome of inappropriate antidiuretic hormone: a post hoc analysis of the SALT‐1 and SALT‐2 trials - Gralla, Richard J. (Cancer Med, 2017)
Hyponatremia is a common electrolyte disorder in cancer patients and has been associated with poor prognosis. A frequent cause of cancer‐related hyponatremia is the syndrome of inappropriate antidiuretic hormone (SIADH). This study was a post hoc subgroup analysis of the SALT‐1 (Study of Ascending Levels of Tolvaptan in Hyponatremia) and SALT‐2 clinical trials. Hyponatremic subjects with SIADH and cancer received the oral selective vasopressin V2‐receptor antagonist tolvaptan (n = 12) or matching placebo (n = 16) once‐daily for 30 days. The initial tolvaptan dose (15 mg) was titrated over 4 days to 30 or 60 mg per day, as needed, according to serum sodium level and tolerability. Baseline serum sodium levels in the SIADH/cancer cohort of the SALT trials was 130 and 128 mEq/L for tolvaptan and placebo, respectively. Mean change from baseline in average daily serum sodium AUC for tolvaptan relative to placebo was 5.0 versus −0.3 mEq/L (P < 0.0001) at day 4, and 6.9 versus 1.0 mEq/L (P < 0.0001) at day 30; the observed treatment effects were similar to those in the overall SIADH population (i.e., with and without cancer) at both time points. Serum sodium normalization was observed in 6/12 and 0/13 subjects at day 4 and 7/8 and 2/6 subjects at day 30 in the tolvaptan and placebo groups, respectively (P < 0.05 for both). Common treatment‐emergent AEs for tolvaptan were consistent with previously reported results. In this post hoc study of the SALT trial population, oral tolvaptan was an effective and safe therapy for the treatment of hyponatremia in subjects with SIADH and cancer.